Bias Berita Pemilihan Presiden & Wakil Presiden di Media Massa Lokal Madura - Lulus Sugeng Triandika (KOMUNIKATIF : Jurnal Ilmiah Komunikasi, 2020)
The alignment of the mass media during the election is common. As a political communication tool, mass media has a strong influence on the public. The topic of the election became favorite news. Both in national and regional scope, mass media make the election as headline news. As a local mass media in Madura, Radar Madura made the arrival of the Presidential & Vice President to Madura as a headline too. Choosing the main news topic and the angle of reporting is the editor's policy. However, what happened was the alignment of the mass media which caused news bias. Therefore, the purpose of this study is to find out how the framing is carried out by Madura Radar. The research will focus on Radar Madura's headlines in the two periods of the election campaigns, namely in 2014-2019 and 2019-2024. The analytical method used is Pan & Kosicky's framing analysis. As a result, Radar Madura tried to be neutral by not highlighting one of the Presidential and Vice President pairs. However, it was found that Madura Radar had made a distinction in framing the news of the arrival of Presidential and Vice Presidential Candidates on Madura Island.